Influence of ITG on organisation performance: the mediating effect of absorptive capacity - Ajayi, Binyamin Adeniyi; Hussin, Husnayati (The Institute of Electrical and Electronics Engineers, Inc., 2016)
Information Technology Governance (ITG) is the deliberate behaviour adopted by senior management in the corporate design of IT for the enterprise use to enable continuous performance. ITG Absorptive Capacity is the organisational competence in recognising, acquiring or creating valuable new business-IT knowledge; assimilating or transforming and applying it, to ensure continuous performance. The study explored past studies to learn how ITG has evolved in the knowledge space. It empirically explores universities in a developing nation context to verify a model of ITG evolved based on earlier efforts. Using survey methodology, it distributed questionnaires to senior management employees drawn from ten universities in Malaysia. Using the multiple regression techniques to analyse the data thus obtained, this study finds that Absorptive Capacity best explains the influence of ITG on performance. This study thus contributes theoretically to knowledge on ITG and absorptive capacity coming up with symbolic links of expected to spur ITG researchers interest. IT should serve as a valuable dynamic capability which when complemented with knowledge capabilities should beget performance. This study thus equipped practitioners with firsthand information on what to consider when talking ITG in universities.